The Arab Spring Five Years Later Volume One Toward Greater Inclusiveness - Ghanem, Hafez (Brookings Institution Press, 2016)
Since the series of uprisings of the Arab Spring began, the debate in Arab countries has focused almost exclusively on politics and questions of national identity. However, it is economic issues that are driving the agenda, and real economic grievances must be addressed in order for the many transitions to succeed.Hafez Ghanem gives a thorough assessment of the Arab Spring, beginning with political developments since the revolutions and changes in the legal and institutional frameworks that affect economies. Arab economies grew at healthy rates before the revolts, but the benefits of economic growth were unfairly distributed. The politically connected reaped great benefits, while educated youth could not find decent jobs, and the poor and middle class struggled to make ends meet. Ghanem argues that Arab countries need to adopt new economic policies and programs that enhance inclusiveness, expand the middle class, and foster growth in undeveloped regions.